The Role of Innovative Work Behavior, Proactive Personality, and Entrepreneurial Alertness on Entrepreneurial Intentions in Higher Education in Region III Cirebon - Nela Pebriani; Annisa Tri Novianti; Sandi Nasrudin Wibowo (PT FORMOSA CENDEKIA GLOBAL, 2024)
The workforce will become more highly educated as the number of educated people rises. Paradoxically, there is a high unemployment rate relative to available resources. This suggests that educated people, including college grads, have little desire or interest in starting their own business. The purpose of this study is to ascertain how prospective undergraduate students in Region III Cirebon feel about their entrepreneurial goals in relation to their innovative work behavior, proactive personality, and entrepreneurial alertness. This study employs quantitative techniques and makes use of SmartPLS 3 software to examine theoretical models. The study's findings indicate that among aspiring undergraduate students in Region III Cirebon, innovative work behavior, a proactive Personality, and entrepreneurial alertness have a favorable and significant impact on Entrepreneurial Intentions.